Mindfulness and the aging brain: a proposed paradigm shift - Prakash, Ruchika Shaurya; De Leon, Angeline A.; Patterson, Beth; Schirda, Brittney L.; Janssen, Alisha L. (Frontiers in Aging Neuroscience, 2014)
There has been a proliferation of cognitive training studies investigating the efficacy of various cognitive training paradigms as well as strategies for improving cognitive control in the elderly. While some have found support for the transfer of training, the majority of training studies show modest to no transfer effects. When transfer effects have been observed, the mechanisms contributing to enhanced functioning have been difficult to dissociate. In this review, we provide a theoretical rationale for the study of mindfulness in older adults as a particular type of training program designed to improve cognitive control by capitalizing on older adults’ acquired behavioral orientation toward higher socioemotional goals. Given the synergistic relationship between emotional and cognitive control processes, the paradoxical divergence in older adults’ functional trajectory in these respective domains, and the harmonious interplay of cognitive and emotional control embedded in the practice of mindfulness, we propose mindfulness training as an opportunistic approach to cultivating cognitive benefits in older adults. The study of mindfulness within aging, we argue, capitalizes on a fundamental finding of the socioemotional aging literature, namely the preferential change in motivational goals of older adults from ones involving future-oriented wants and desires to present-focused emotion regulation and gratification.